Development of an Auditory Rehabilitation Tool for children with Cochlear Implants through a Mobile-Based VR and AR serious game - Hatzigiannakoglou, Paul D; Okalidou, Areti (International Journal of Online and Biomedical Engineering (iJOE), 2019)
It is known that the development of auditory skills in children with hearing loss, who use assistive listening devices, requires training and practice. The aims of this research were a) to describe an auditory training software developed in order to help children with cochlear implants and/or hearing aids improve their auditory skills and monitor their performance, and b) to demonstrate the usability of the auditory training tool. The software is mobile-based and uses VR (Virtual Reality) and Immersive technology. In order to use it, the user must wear a VR headset. This technology was adopted because these devices are considered to be innovative, and are especially popular among children. The software was tested on fourteen hearing-impaired children. Eleven of these children use a cochlear implant and three use hearing aids. The results of this research show that the children with hearing loss were able to play the game successfully. This positive outcome supports the use of VR and Immersive technology as Auditory Training Tools.